2020
DOI: 10.1097/md.0000000000023051
|View full text |Cite
|
Sign up to set email alerts
|

Asthma susceptible genes in children

Abstract: Supplemental Digital Content is available in the text

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…The East Asian population showed a lower risk of asthma association in all the models used, and relative to the other ethnicity subgroups, it showed the lowest risk, however, the association is still present. Our results are inconsistent with past meta-analyses since most studies about Chinese populations reported the association of IL-13 SNP rs20541 with asthma risk, instead of rs1800925 [ 16 , 45 , 46 ]. Though previous studies did not associate the polymorphism with the progression of the disease [ 29 ], our findings reported a positive association with asthma; hence, it is suggested that genetic diversity might be present in the East Asian population.…”
Section: Discussioncontrasting
confidence: 99%
“…The East Asian population showed a lower risk of asthma association in all the models used, and relative to the other ethnicity subgroups, it showed the lowest risk, however, the association is still present. Our results are inconsistent with past meta-analyses since most studies about Chinese populations reported the association of IL-13 SNP rs20541 with asthma risk, instead of rs1800925 [ 16 , 45 , 46 ]. Though previous studies did not associate the polymorphism with the progression of the disease [ 29 ], our findings reported a positive association with asthma; hence, it is suggested that genetic diversity might be present in the East Asian population.…”
Section: Discussioncontrasting
confidence: 99%
“…Among childhood, asthma is accepted as the most common chronic disease. Recently, accumulating evidence researched the function role of VDR gene polymorphism in childhood asthma, and four SNPs, including BsmI (rs1544410), ApaI (rs7975232), FokI (rs2228570), and TaqI (rs731236), were the main gene locuses (3,29). Based on the meta-analysis, our data showed that FokI (rs2228570) could significantly affect the risk of childhood asthma across co dominant model and dominant model, especially among Caucasians.…”
Section: Discussionmentioning
confidence: 74%
“…Particular genes directly impact the immune response, both humoral and cellular. For instance, IL-13+2044G/A, IL-4-590C/T polymorphisms are associated with an increased risk of childhood asthma development ( 20 ).…”
Section: Immunological Genetic and Epigenetic Factors Of Allergy Deve...mentioning
confidence: 99%